Generalized k–step Jacobsthal numbers coding and decoding method - Yadav, Arun Kumar; Pruthi, Manju (Journal of discrete mathematical sciences & cryptography, 2023)
In this article, we create a coding/decoding method utilizing the generalized k-step Jacobsthal numbers and the relation between the components of the code matrix and error detection and correction have been established for all value of k. The method’s accuracy is 93.33 percent for k = 2, the method’s accuracy is 99.80 percent for k = 3 and the method accuracy is 99.998 percent for n = 4. In general, the accuracy of the approach improves with each successively higher value of n. We give two examples of generalized k – step jacobsthal sequences via blocking algorithm and solve these illustrations using python.